STRUKTURALISME DALAM GANDRUNG BANYUWANGI: PAKAIAN DAN GERAKAN (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2024)
The presence of Gandrung as a typical art of Banyuwangi is known to have helped build structures that show the behavior and mindset of the Using people. This can be seen in every arrangement of movements and clothing this art uses. For this reason, this research was prepared to analyze the structuralism of Gandrung Banyuwangi through clothing and movement. The research method used is qualitative through interview techniques and reading literature from previous research. The analysis process was carried out using Saussure's structuralism approach. The results of the study show that as a typical art, Gandrung Banyuwangi is unique in the arrangement of clothing and movements presented, where each knick-knack and act presented symbolizes uniqueness for the community that formed it, which refers to Gandrung not only existing as an entertaining art but also "symbol of struggle" for the Using people. Therefore, it can be concluded that Gandrung as an art is also composed of ornaments that show the uniqueness of Using society based on behavior that has been constructed from the creation of old habitus, which is combined with the complex thoughts of the people, which are then present in Gandrung's clothing and movements.